2022
DOI: 10.3389/fphar.2022.852631
|View full text |Cite
|
Sign up to set email alerts
|

The Binding Mode to Orthosteric Sites and/or Exosites Underlies the Therapeutic Potential of Drugs Targeting Cannabinoid CB2 Receptors

Abstract: The classical terms agonists and antagonists for G protein coupled receptors (GPCRs) have often become misleading. Even the biased agonism concept does not describe all the possibilities already demonstrated for GPCRs. The cannabinoid CB2 receptor (CB2R) emerged as a promising target for a variety of diseases. Reasons for such huge potential are centered around the way drugs sit in the orthosteric and/or exosites of the receptor. On the one hand, a given drug in a specific CB2R conformation leads to a signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…However, our modeling studies suggested a mechanism for the terpenes to bind and activate the A 2A R in the orthosteric binding pocket. One possibility is that the terpenes bind to a subcompartment of the orthosteric site that permits orthosteric activation but avoids radioligand competition; analogous findings have been described for cannabinoids that compete with 3 H-WIN55,212 but not 3 H-CP55,940 at the CB1R (discussed in [54]). Another possibility is that our terpenes bind the orthosteric site in a competing pose with 3 H-ZM241385 but have unfavorable pharmacodynamic features (affinity, K ON/OFF , etc.)…”
Section: Discussionmentioning
confidence: 74%
“…However, our modeling studies suggested a mechanism for the terpenes to bind and activate the A 2A R in the orthosteric binding pocket. One possibility is that the terpenes bind to a subcompartment of the orthosteric site that permits orthosteric activation but avoids radioligand competition; analogous findings have been described for cannabinoids that compete with 3 H-WIN55,212 but not 3 H-CP55,940 at the CB1R (discussed in [54]). Another possibility is that our terpenes bind the orthosteric site in a competing pose with 3 H-ZM241385 but have unfavorable pharmacodynamic features (affinity, K ON/OFF , etc.)…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, if an allosteric mechanism is contributing to the kinetic signalling profiles observed, the ligands might be acting “dualsterically” with an allosteric site in close spatial proximity to the orthosteric site, have transient allosteric interactions, or be acting via dual binding at the orthosteric site and a distant allosteric site on the same or dimerised receptor protomer [ 34 , 35 , 36 , 37 ]. Various allosteric sites in CB2 have been predicted, including at least one near the orthosteric site [ 31 , 38 , 39 , 40 , 41 ]. Interestingly, all the test compounds we studied had a considerably higher signalling potency:affinity ratio than CP55,940, which could also indicate involvement of an allosteric mechanism in the transduction of signalling for the test compounds [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…When these ligands interact with the CB 2 receptor, they can modulate its function, leading to a range of potential therapeutic benefits [ 48 ]. For instance, cannabidiol acts as a negative allosteric modulator of CB 2 R, inducing conformational changes in such a way that biases the effect of orthosteric agonists [ 49 ].…”
Section: Functional Role Of Cb 2 R In Strokementioning
confidence: 99%